Implementasi Interpolasi Fractal Untuk Pembesaran Skala Pada Citra Screen Capture CCTV - Putri Nurul Hasanah (JURIKOM (Jurnal Riset Komputer), 2020)
Various types of image processing that can be done by computers today such as image enlargement, image quality improvement and sharpening of an image are one of the fields that are quite popular today. Sharpening an image is very necessary so that someone can see and observe clearly the object of the image and the absence of interference. An image can have damage to some parts or blocks of pixels in the sending or storage process. This damage is the main form of error in the image, for example the image of CCTV Capture. The problem that is often faced when we want to see a CCTV recording is the obscurity of an object image that we want to see. If the Screen Capture and zoom in will be increasingly unclear the image object. The results of this Screen Capture image have a better level of sharpness if it is enlarged directly, the Screen Capture is usually used as evidence and so on. This image improvement is done by the operation process of the selection point of the results of the CCTV Screen Capture image that is used as a sample. After the Screen Capture image selection results are obtained then the image is in Grayscale to make a uniform pixel value, the next process is the process of enlarging the image of the Screen Capture image by adding new pixels. This is done by inserting the new pixel points between the points where the pixel value has been set directly from the original image. To overcome these problems requires the Fractal Interpolation method to improve image quality enhancement. With this method it is expected to be able to solve the problem of improving the image quality enlargement of the results of the CCTV Capture Screen. This research was conducted to implement the process of improving image quality magnification based on the Fractal Interpolation method.